Dangers of using activated charcoal for teeth whitening (Research, Society and Development, 2022)
In society the search for the perfect smile has become increasingly recurrent. In recent years, the use of activated charcoal has been observed with the promise of teeth whitening, however there is no scientific evidence that this material has bleaching action. To perform an analysis of the literature on the dangers of using Activated Carbon for dental bleaching. The literature review was conducted through the databases: Scielo, Pubmed, and Lilacs.The following keywords were used as search strategy: Dental Whitening, Toothpastes, Activated Charcoal, Abrasion, Dental Bleaching. Among the inclusion criteria, studies published in Portuguese between 2010 and 2021 were selected. Exclusion criteria include articles that did not present relevant information on the proposed theme. Although some studies show that these products do not pose an additional risk to patients, most authors report that it is preferable to use products that have a proven bleaching effect. Activated carbon is a mineral of high abrasive capacity that increases the roughness of the dental surface and also alters the surface of restorations in composite resin.It can cause dental conditions such as tooth abrasion and erosion and increases susceptibility to periodontal disease and gingival recessions. The use of activated charcoal has caused several dental wear becoming a disease for oral health and its use as a bleaching agent has no scientific proof.